EFEKTIVITAS MODEL PEMBELAJARAN BLENDED LEARNING DENGAN PENDEKATAN STEM DALAM KEMAMPUAN BERPIKIR KRITIS SISWA - suhastantin safianti; Endang Suprapti; Shoffan Shoffa (Cartesian: Jurnal Pendidikan Matematika, 2022)
This study aims to demonstrate the effectiveness of the application of the blended learning model with the STEM (Science, Technology, Engineering, and Mathematics) approach to the material of a two-variable linear equation system (SPLDV) class VIII-E SMP Negeri 18 Surabaya. The type of research used is descriptive quantitative research. The instruments used are critical thinking ability test questions, student activity observation sheets, teacher ability observation sheets in managing learning, and student response questionnaires. The results showed that the blended learning learning model with the STEM (Science, Technology, Engineering, and Mathematics) approach in class VIII-E of SMP Negeri 18 Surabaya was not effective because learning outcomes in students' critical thinking skills obtained an average N-Gain score of 0.28 is categorized as low. Although the other three aspects have met the effective criteria, it is indicated by the effectiveness of student activities in all meetings getting an average of 89.9% which is categorized as very strong, the effectiveness of the teacher's ability is on average 98.4% in the very good category, and student responses to learning show very positive response. This should affect student learning outcomes but in reality it does not affect it, this is because students are less able to recognize and formulate problems, have not been able to solve problems correctly using all SPLDV methods (elimination, substitution, and mixture). Keywords: Blended Learning, Effectiveness, Critical Thinking Ability, STEM Approach